Presidential Doctrines and Strategies of American Foreign Policy from 1947 To 1965 - Marek Hampl (Communications - Scientific letters of the University of Zilina, 2010)
This paper analyzes the most important doctrinal statements of American foreign policy from 1947 to 1965. Attention will be primarily focused on The Truman Doctrine, the writings by George F. Kennan, The Eisenhower Doctrine and the Johnson Doctrine. These statements of US foreign policy constituted broader strategy of containment of Communism during the first two decades of the Cold War. I shall argue that these declared doctrines and strategies provided theoretical background for containment of the Soviet influence on a global scale. Also, the doctrines and strategies provided basis for active involvement of the United States in the regions where there was an imminent danger of Communist expansion.